THE DIFFI-HELLMANA PROTOCOL ON THE SET OF SINGULAR SIMPLE NUMBERS - Білецький, А.; Семенюк, О. (Science-based technologies, 2012)
Introduced the class of the singular prime numbers, based on which proposed the algorithm of significantly reduce computing time spent on the choice of suitable values for the Diffie–Hellman protocols.